Research on badminton players' specialized fitness training - Liu, Jiamin; He, Qiu (Cambridge Sport Science, 2025)
The relationship between specialized physical fitness and skills has always been a controversial issue in China's badminton community. The components of badminton's specialized physical fitness include specialized speed, strength, endurance, and agility. The relationship between the four basic qualities of strength, speed, endurance, and agility is summarized as follows: speed is the key, strength and agility are the foundation, and endurance is the guarantee.